Pengaruh Kepemimpinan Kepala Desa Terhadap Peningkatan Kesadaran Masyarakat Dalam Membayar Pajak Bumi dan Bangunan di Desa Kaayuran Bawah Kecamatan Langowan Selatan Kabupaten Minahasa - Kalalo, Frisilia Jolanda; Tulusan, Femmy; Ruru, Joorie (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: This study berwal of experiences to the principal that is, the extent to which the influence of the leadership of the head of the village to increase public awareness in paying taxes on land and buildings in the village kaayuran south district under the District Langowan minahasa. Thus this study aims to analyze the influence of the leadership of the head of the village to increase public awareness in paying taxes on land and buildings in the village kaayuran south district under the District Langowan minahasa. This study uses quantitative methods to approach the descriptive analysis of data and information collected through questionnaires distributed to the technique 53 respondents were equipped with observation technique by applying the technique of frequency tables, analysis of product moment and simple linear regression. Based on the results of the data analaisi known that the answer respoenden on leadership clod village is in a class interval between 22-25 with a .ï‚±frequency of 25 respondents, or 47.2% This indicates that the average score of variable Leadership Village Head (X) are in the category of "high" while in the pay of the UN Awareness (Y) beada the class interval between 22-25 with a frequency of 23 ï‚±respondents, or 43.4% , It can be interpreted that the average scores in the Public Awareness variable pay land and building tax (Y) in the village of Down District Langowan Kaayuran the South are in the category of "high" It can be concluded that the Leadership Village Head Down Kaayuran Southern District Langowan very ignifikan positive effect on the level of public awareness in paying property tax The village head in implementing transformational leadership style tends to rely more effective in raising public awareness and building earth to pay tax, in particular in Kaayuran village Down South Minahasa District Langowan. Keywords: Leadership village head, Awareness In Pay Property Tax